2021
DOI: 10.48550/arxiv.2107.07727
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Electromagnetic Field in Gravitational Wave Interferometers

Thomas Mieling,
Piotr T. Chruściel,
Stefan Palenta

Abstract: We analyse the response of laser interferometric gravitational wave detectors using the full Maxwell equations in curved spacetime in the presence of weak gravitational waves. Existence and uniqueness of solutions is ensured by setting up a suitable boundary value problem. This puts on solid ground previous approximate calculations. We find consistency with previous results obtained from eikonal expansions at the level of accuracy accessible to current gravitational wave detectors.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…To detect both of these results we have to re-design an experiment which is work in progress [6]. Further, in this paper, the boundary conditions as required in a realistic interferometric set up [13] have to be discussed. However, as we observe to measure the new 'frequency' in an earth experiment one has to use Masers and this is being investigated [6].…”
Section: Discussionmentioning
confidence: 99%
“…To detect both of these results we have to re-design an experiment which is work in progress [6]. Further, in this paper, the boundary conditions as required in a realistic interferometric set up [13] have to be discussed. However, as we observe to measure the new 'frequency' in an earth experiment one has to use Masers and this is being investigated [6].…”
Section: Discussionmentioning
confidence: 99%
“…In [19] we have observed that one can solve uniquely the Maxwell equations by describing the laser, and the mirrors, as a boundary-value problem for the Maxwell equations with analytic boundary data given on an infinite timelike hyperplane in a space-time with an analytic metric (13) g…”
Section: Interferometersmentioning
confidence: 99%